Technical and Economical Evaluation of Solar PV System for Domestic Load in Pakistan: An Overlook Contributor to High Tariff and Load Shedding - Shoaib Ahmed Shaikh; Abdul Majeed Shaikh; Muhammad Fawad Shaikh; Shakil Ahmed Jiskani; Qasir Ali Memon (Sir Syed University Research Journal of Engineering and Technology, 2022)
Despite the addition of generation sources to the installed capacity, Pakistan is facing frequent load-shedding, electricity interception, and a high tariff rate. Focusing on the said issues, an investigation has been completed of all the Distribution Companies (DISCOs) along with statistics like yearly losses, recovery, and tariff are reviewed to analyze the power network. It is a clear scenario that there is still a gap between supply and demand, and the generation major part is from fossil fuels which result in the high tariff due to unvarying fuel prices and environmental issues. This in fact has become uneconomical for the domestic users to utilize electricity from the power companies. Apart from this, Pakistan is blessed with a high potential for renewable energy resources, which is a good indication from an economic and environmental point of view but unfortunately, its usage is less. Keeping in view all statistics and key issues, this article focusses on the economic and technical evaluation on different cases like load running on Water and Power Development Authority (WAPDA), load on Solar PV system with backup, load on Solar PV system without backup, and Utility with a generator backup. Various economic techniques are used as Net Present Value (NPV), Payback Period (PBP), and Internal Rate of Return (IRR) to analyze and select the cost-effective solution. From the analysis, utilization of load from the Utility company and PV systems were compared. The PV system is the most economical and reliable system when compared with other cases.